ANALISIS AKUNTANSI SYARIAH SEBAGAI SISTEM INFORMASI DI INDONESIA (Jurnal Riset Akuntansi, 2022)
Accounting is an information system that identifies, records, summarizes, classifies, and reports data related to economic events to enable users to make informed decisions. While in sharia accounting, the word 'sharia' generally means the path that we must go through. A Muslim certainly cannot escape from Islam. after saying the shahada, he must follow the rules of Allah and the Messenger," he added. This research is alibrary research, namely a special exploration where the study is carried out by following and evaluating literary works and which focuses on examining library materials. The information investigation strategy used is a substance examination technique or also known as content examination, which is an exploratory technique used for an intelligent and substantial resolution of information given the unique circumstances. The results of this study indicate that Islamic accounting is one of the efforts to rearrange current accounting in a humanist and dignified structure. The reason for holding sharia accounting is to develop business with humanist, emancipatory, supernatural and philosophical knowledge. Therefore, through sharia bookkeeping, social reality will be built through satisfying videos of monotheism and divine accommodation, all of which are equipped with the point of view of khalifatullah fil ardh. Basically the sharia accounting information system underlines the characteristics of Islam both in the object of the bookkeeping and the data frame, so that the Islamic accounting data framework has an extraordinary obligation in moral matters.